A case of multiple fibroid uterus, complete placenta praevia, antepartum haemorrhage, myomectomy and obstetric hysterectomy: a near miss - Devi, L. Thulasi; Mahajan, Shivani; R. S., Athul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
An interesting case of young unbooked, unregistered, primigravida with multiple fibroid uterus, placenta praevia type IV, presented with APH in haemorrhagic Shock, impacted large fibroid in Lower Uterine Segment and Multiple fibroids on Anterior wall, fundus for which myomectomy was performed. Preterm Caesarean Section with extremely low birth weight infant delivered followed by life-saving Emergency Obstetric hysterectomy. She had uneventful recovery without any complications of massive transfusion or surgery. Case is being reported as an obstetric near miss.